Advantages and Disadvantages of Chatgpt in Science Learning: A Systematic Literature Review - Ahmad Maulid Asmiddin; Pradicta Nurhuda; Ruth Megawati (Jurnal Penelitian Pendidikan IPA, 2023)
Currently many forms of sophisticated technology are used by many people. This of course cannot be separated from the existence of artificial intelligence. One form of sophisticated technology is Chat GPT which was developed by Open AI. Science as a collection of knowledge is the result of human scientific creative activity. The results of scientific creative activities will produce knowledge in the form of facts, concepts, principles, laws, and theories. Science is a human activity characterized by thought processes that take place in the human mind. With developing technology, one of which is Chat GPT, it will make the current science learning process easier. The research aims to examine the advantages and disadvantages of Chatgpt in Science Learning: Systematic Literature Review. The review was conducted based on state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. The results of this research explain that. GPT chat has several uses, advantages, and disadvantages in science learning. For this reason, GPT chat must be used as wisely as possible, so that there are no mistakes in its application in science learning or other learning.